Me ajuda por favorrrrrrrrr
Anexos:
![](https://pt-static.z-dn.net/files/d91/e6c912a29a2f61851a3a2b36597aaac1.jpeg)
Soluções para a tarefa
Respondido por
0
Explicação passo-a-passo:
Simplificando:
(a³-a²-9a+9) / a²-9
= (a²-(a-1) -9(a-1)) / a²-9
= ((a-1).(a²-9)) / (a²-9)
= a - 1
sendo a = -1, temos:
a-1 = -1 -1 = -2
Perguntas interessantes
História,
7 meses atrás
Matemática,
7 meses atrás
Português,
7 meses atrás
Matemática,
8 meses atrás
Ed. Física,
8 meses atrás
Física,
1 ano atrás
Matemática,
1 ano atrás